Emergence and detection of gastro‐enteric virulence genes in non‐pathogenic Vibrio cholerae: Implications for public health and water safety in African developmental regions - Bright Esegbuyota Igere (Medicine Advances)
Abstract Background Water, an indispensable component of life, has in recent times been associated with the distribution/spread of gastro‐enteric diseases especially as safe water is a concern in Southern, Eastern and Western African developmental regions. Methods This study evaluated the molecular fingerprints of potential gastro‐enteric associated virulence genes of 58 somatic antigen non‐agglutinating Vibrio cholerae 1/139 (SA‐NAG‐Vc‐1/139) strains from domestic water sources. Strains were isolated and characterized applying both culture‐based‐microbiological techniques and molecular‐fingerprinting of target‐specific identification genes using simplex/multiplex PCR assay and ERIC‐PCR fingerprints. Results Our study revealed diverse gene‐based indices vis T3SS (29/58, 50.00%), T6SS (33/58, 56.9%), rtxA (37/58, 63.79%), rtxC (12/58, 20.69%), NAG‐stn/sto (13/58, 22.41%), prtV (17/58, 29.31%), hlyA (41/58, 70.69%), nanH (40/58, 68.97%), mshA (44/58, 75.86%), chxA (37/58, 63.79%), hapA (17/58, 29.31%), ace (22/58, 37.93%), and cep (20/58, 34.48%) etc. Such results show that 53.45% (31/58) of isolates harboured more than three virulence associated genes while nanH, mshA, chxA, T6SS, T3SS, rtxA, hlyA, mshA, chxA, ace and cep fingerprints were detected predominantly with corresponding ilea‐loop test positive strains. ERIC‐PCR also showed multiple target specific repetitive intergenic consensus sequence regions ranging from 2 to 8. Conclusions This is an indication that the previously known non‐pathogenic strains now harbour potential gastro‐enteric virulence which may be controlled by more than one virulent gene dynamics. It also suggests a current potential shift in the virulence dynamics of V. cholerae strains recovered from the study area and a re‐evaluated view of the previously non‐pathogenic V. cholerae strains. Furthermore, the presence of such genes in SA‐NAG‐Vc‐1/139 strains indicates a potential public health related concern. Although these detected potential gastro‐enteric associated genes may be implicated in sporadic gastroenteritis, our result has re‐emphasized their probable public health concern as they may be involved in both endemic and severe gastroenteritis cases, which suggests the need for water routine monitoring or surveillance.